High interindividual variability in LDL-cholesterol reductions after inclisiran administration in a real-world multicenter setting in Germany - Makhmudova, Umidakhon; Schatz, U.; Perakakis, N.; Kassner, U.; Schumann, F.; Axthelm, C.; Stürzebecher, P.; Sinning, D. L.; Doevelaar, A.; Rohn, B.; Westhoff, T.; Vogt, A.; et al. (Clinical research in cardiology, 2023)
Low-density lipoprotein cholesterol (LDL-C) is the main therapeutic target in the treatment of hypercholesterolemia. Small interfering RNA (siRNA) inclisiran is a new drug, which targets PCSK9 mRNA in the liver, reducing concentrations of circulating LDL-C. In randomized trials, inclisiran demonstrated a substantial reduction in LDL-C. The German Inclisiran Network (GIN) aims to evaluate LDL-C reductions in a real-world cohort of patients treated with inclisiran in Germany.
Online veröffentlicht: 9. Juli 2023
Gesehen am 01.08.2024